ChemInform Abstract: Synthesis, Crystal Structure and Antitumor Activities of the Dimeric Silicotungstate Containing Cobalt: Na5K7 [β‐SiCo2W10O36(OH)2 (H2O)2]·39.5H2O. Issue 7 (22nd February 2013) - Tan, Rongxin; Pang, Xiaohong; Wang, Hui; Cui, Shuxin; Jiang, Yaping; Wang, Cheng; Wang, Xiaohong; Song, Wenzhi
Abstract Red block crystals of the title compound are prepared by slow evaporation of an aqueous solution containing Co(OAc)2, K8[γ‐SiW10O36], NaHCO3, and KCl (10 °C, 14 d; 47% yield).